Problem-solving and coping in family adaptation of children with Down Syndrome - Braga,Patrícia Pinto (2021)
ABSTRACT Objective: To analyze problem-solving and coping strategies of parents of children with Down Syndrome in family adaptation. Method: This is a qualitative research that used the Resiliency Model of Family Stress, Adjustment, and Adaptation. Participants were mothers and/or fathers from 40 families of children aged 1 to 7 years diagnosed with DS. Directed content analysis was performed, supported by software and considering a code dictionary. Results: Problem-solving and coping proved to be a set of actions, behaviors, efforts, and communications that contributed to family adaptation and favored balance between the demands imposed by Down Syndrome and the acquisition of resources by the family. Conclusion: In the first moment, which corresponds to the time of news or diagnosis of the syndrome and the first days after birth, internal and external resources, which represent coping, are developed to accept and refocus ideas and feelings towards Down Syndrome. Over time these resources have an effect and cause changes in family functioning patterns and in the relationship of these families with the outside world, as they seek child development.